Electronic Enlightenment or the Digital Dark Age? Anticipating Film in an Age Without Film. - Enticknap, Leo (Quarterly Review of Film & Video, 2009)
The article discusses the distribution and exhibition of commercially produced moving images through impending obsolescence of photographic film. It notes an argument that the distribution will urge critics, scholars, and archivists to address the technical specificity of moving image media. It mentions considerations to the cultural status and meaning of the product itself commenting on the contribution of the word "film" to a gradual transition form referring to a specific form of photochemical imaging technology.